Mercury poisoning: prevalence, knowledge and frequency of gold panning and doing retort among alluvial gold panners in Chiweshe and Tafuna communal lands in Zimbabwe. - Matchaba-Hove, Reginald; Siziya, S.; Rusakaniko, S.; Kadenhe, R.M.; Dumbu, S.; Chirenda, J. (2016)
Abstract OBJECTIVES: